Observations of parturition in humpback whales (Megaptera novaeangliae) and occurrence of escorting and competitive behavior around birthing females. Issue 2 (7th September 2021) - Ransome, Nicola; Bejder, Lars; Jenner, Micheline; Penfold, Gavin; Brosig, Violeta J.; Kitson, Craig; Skjothaug, Rebecca; Neilson, Emma; Loneragan, Neil R.; Smith, Joshua N.
Abstract: Documented cases of cetacean births in the wild are rare. While there are currently no direct observations of a complete humpback whale birth, they are one of the few large whale species where observers have been present during a birthing event. We compiled eye‐witnessed accounts of all known humpback whale birthing events and found nine well‐documented cases globally (three published and six "new" unpublished). In two‐thirds of the accounts another "escort" whale was present and in close association with the birthing female, and of these, most cases involved multiple escorts ( n  = 4). We describe details of birthing events, including mother, neonate and escort(s)' behavior, neonate appearance, and discuss reasons for escort presence during parturition. We note that immediately postpartum: (1) blood and/or placenta were not always apparent during above water observations, (2) females often (but not always) supported calves at the surface, (3) constant travel and tail slapping were typical neonate behaviors, (4) two cases of temporary calf abandonment (<10 min), and (5) evidence of shark scavenging (of placenta) and possible predation attempts (of neonate). Lastly, we suggest curled tail flukes as an additional trait for identifying neonates and note that fetal folds are not always evident in newborn humpback whales.